Telehealth reform post–public health emergency: crucial next steps. Issue 2 (4th March 2023) - Thomas, Devon; Garate, David; Fu, Shangyi; Bashir, Amna; Moss, Nathaniel; Nair, Muktha
Abstract: As the pandemic made it unsafe for providers and patients to meet in person, the US government implemented key temporary telehealth waivers in March 2020 that expanded Medicare telehealth coverage dramatically. Some of the most significant changes included the removal of location restrictions so that patients and providers could engage in telehealth from their homes, full provider reimbursement for telehealth visits, coverage for more medical specialties and types of practitioners such as occupational and physical therapists, and the allowance of telehealth prescription of controlled substances. The waivers will end when the government removes the federal status of a public health emergency, which is expected to occur in 2023. Nearly 64 million Medicare patients are at risk of losing most modalities of telehealth access. We present current legislation that could combat this "telehealth cliff" and defend the position that Medicare telehealth access should remain permanently expanded.